Comprehensive Cardiovascular Magnetic Resonance Assessment in Patients With Sarcoidosis and Preserved Left Ventricular Ejection Fraction. (November 2016) - Greulich, Simon; Kitterer, Daniel; Latus, Joerg; Aguor, Eissa; Steubing, Hannah; Kaesemann, Philipp; Patrascu, Alexandru; Greiser, Andreas; Groeninger, Stefan; Mayr, Agnes; Braun, Niko; Alscher, M. Dominik; et al.
Abstract : Background—: Cardiac sarcoidosis (CS) may manifest as arrhythmia or even sudden cardiac death. Because patients with CS often present with nonspecific symptoms, normal electrocardiography, and preserved left ventricular ejection fraction, a reliable diagnostic tool for the work-up of CS is needed. Late gadolinium enhancement–cardiovascular magnetic resonance has proven diagnostic value in CS but has some limitations that may be overcome by adding newer cardiovascular magnetic resonance mapping techniques. The aim of our study was to evaluate a comprehensive cardiovascular magnetic resonance protocol, including late gadolinium enhancement and mapping sequences in sarcoid patients with no symptoms or unspecific symptoms and preserved left ventricular ejection fraction. Methods and Results—: Sixty-one sarcoid patients were prospectively enrolled and underwent comprehensive cardiovascular magnetic resonance imaging. Twenty-six healthy volunteers served as control group. Mean left ventricular ejection fraction was 65%; late gadolinium enhancement was only present in sarcoid patients (n=15). Sarcoid patients had a higher median native T1 (994 versus 960 ms; P <0.001), lower post contrast T1 (491 versus 526 ms; P =0.001), expanded extracellular volume (28 versus 25%; P =0.001), and higher T2 values (52 versus 49 ms; P <0.001) compared with controls. Among patients with values higher than the 95% percentile of healthy controls, most significant differences were observed for native T1 and T2 values. Most of these patients were late gadolinium enhancement negative. Conclusions—: Patients with sarcoidosis demonstrate higher T1, extracellular volume, and T2 values compared with healthy controls, with most significant differences for native T1 and T2. While promising, the clinical significance of the newer mapping techniques with respect to early diagnosis and therapy of CS will have to be determined in future studies. Abstract : Supplemental Digital Content is available in the text.